Problem solved? An individual ratio between Point-Of-Care and venous INR values in two patients with Antiphospholipid Syndrome: two case reports - Bettina C Geertsema-Hoeve; Massimo Radin; Savino Sciascia; Rolf T. Urbanus; Albert Huisman; Josine Borgsteede-de Wilde; Maarten Limper (TH Open)
Antiphospholipid syndrome (APS) is a rare autoimmune disorder characterized by thromboembolic and obstetric complications in the presence of persistent antiphospholipid antibodies (aPL). Treatment aims to prevent recurrent thrombosis, primarily using anticoagulation therapy with vitamin-K antagonists (VKA). Monitoring of VKA therapy relies on the International Normalized Ratio (INR), which can be assessed using point-of-care (POC) testing. However, in a subset of APS patients with a high-risk aPL profile, the POCT-INR is falsely elevated, which might lead to underdosing of VKA and subsequent high risk of recurrent thrombosis. This case report describes two female patients with triple-positive thrombotic APS receiving VKA therapy. Both patients underwent biweekly paired INR measurements via POCT-INR and venous INR methods. Despite significant discrepancies, a strong individual linear correlation was observed: r=0.77 (95%CI 0.54 – 0.99, p<0.001) and r=0.93 (95%CI 0.88 – 0.97, p<0.001), respectively. These findings suggest that individualized correction factors could be developed to improve the accuracy of POCT-INR measurements, thereby optimizing VKA dosing in these patients.